1999
DOI: 10.1002/1529-0131(199907)42:7<1538::aid-anr29>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of annexin I on synovial inflammation in rat adjuvant arthritis

Abstract: Annexin I is a key endogenous inhibitory mediator of arthritis via mechanisms that include inhibition of cytokine and effector molecule production. Moreover, a synthesis-independent depletion of intracellular annexin I by extracellular antibody supports the hypothesis that externalization of annexin I is involved in its mode of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 44 publications
3
66
0
1
Order By: Relevance
“…For example, our previous studies demonstrated that deficiency of AnxA1 significantly exacerbated antigen-induced arthritis in mice, and reduced the inhibitory effect of glucocorticoids in this model . This finding is compatible with the exacerbation of experimental arthritis in rats in response to neutralization of AnxA1 using a specific antibody (Yang et al, 1999). Recent studies have also revealed that mediation of glucocorticoid effects by AnxA1 is associated with effects on the expression of glucocorticoid-induced anti-inflammatory genes, such as MAPK phosphatase-1 and glucocorticoid-induced leucine zipper .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…For example, our previous studies demonstrated that deficiency of AnxA1 significantly exacerbated antigen-induced arthritis in mice, and reduced the inhibitory effect of glucocorticoids in this model . This finding is compatible with the exacerbation of experimental arthritis in rats in response to neutralization of AnxA1 using a specific antibody (Yang et al, 1999). Recent studies have also revealed that mediation of glucocorticoid effects by AnxA1 is associated with effects on the expression of glucocorticoid-induced anti-inflammatory genes, such as MAPK phosphatase-1 and glucocorticoid-induced leucine zipper .…”
Section: Introductionsupporting
confidence: 77%
“…AnxA1 has been shown to ameliorate disease in several animal models of inflammation, including arthritis (Yang et al, 1999;2013b;Patel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies against AnxA1 impaired the anti-inflammatory effects of GCs on carageenininduced paw oedema (Duncan et al, 1993), ischaemia-reperfusion injury (D'Amico et al, 2000) and adjuvant-induced arthritis (Yang et al, 1999). Inflammatory responses of an AnxA1 null mouse strain were exaggerated (Chatterjee et al, 2005;Hannon et al, 2003;Warne et al, 2006;Yang et al, 2004), and cells derived from these mice overexpressed COX-2, IL-1β and -6 in response to pro-inflammatory stimuli (Croxtall et al, 2003;Damazo et al, 2006;Hannon et al, 2003;Yang et al, 2006;Yona et al, 2004;Yona et al, 2005), suggesting that AnxA1 is an endogenous inhibitor of inflammatory responses .…”
Section: A Clarkmentioning
confidence: 99%
“…In animals with adjuvant-induced arthritis, annexin I neutralization was shown to exacerbate disease severity and increase synovial production of prostaglandin E 2 and TNF␣ (4). In both of these models, annexin I was shown to be necessary for the therapeutic effect of exogenous glucocorticoids, in that monoclonal antibody antagonism of annexin I prevented the antiinflammatory effect of dexamethasone (3,4). Annexin I is also necessary for the effect of glucocorticoids on the generation of nitric oxide by synovial macrophages from animals with adjuvant arthritis (2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, annexin I is translocated to the cell surface in response to glucocorticoids (5,6). Moreover, antiannexin I antibodies, which are unable to penetrate the cell, deplete intracellular annexin I and significantly reverse the antiinflammatory effects of glucocorticoids (3,4). Finally, the blockade of cell surface annexin I binding sites by inactivated annexin I protein prevents the biologic activity of extracellular annexin I peptide (7).…”
mentioning
confidence: 99%